Intelligent Control and Innovative Computing - Ao, Sio Iong.; Castillo, Oscar; Huang, He.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
In the lightning-fast world of intelligent control and cutting-edge computing, it is vitally important to stay abreast of developments that seem to follow each other without pause. This publication features the very latest and some of the very best current research in the field, with 32 revised and extended research articles written by prominent researchers in the field. Culled from contributions to the key 2011 conference Advances in Intelligent Control and Innovative Computing, held in Hong Kong, the articles deal with a wealth of relevant topics, from the most recent work in artificial intelligence and decision-supporting systems, to automated planning, modelling and simulation, signal processing, and industrial applications. Not only does this work communicate the current state of the art in intelligent control and innovative computing, it is also an illuminating guide to up-to-date topics for researchers and graduate students in the field. The quality of the contents is absolutely assured by the high profile of the 250 members of the IMECS (International Multi-Conference of Engineers and Computer Scientists) committees who come from more than 30 countries and who supervised the selection of papers.
Reciprocally Convex Approach for the Stability of Networked Control Systems.- Space Robot Control for Unknown Target Handling -- Multi-Sensor Architectures -- Five-axis Curve Machining for Computer Control Machine Tools -- Approximate Linear Quadratic Regulator Problems and its Application to Optimal Control in Discrete-time LTI Systems -- Structured Robust Control for MIMO Systems Using Artificial Intelligent Techniques -- Fuzzy Robust Trajectory Tracking Control of WMRS -- Balanced Performance/Robustness PID Design -- Hybrid Genetic Algorithm Optimization of Distributing Networks – A Comparative Study -- Cooking-step Scheduling Algorithm for Simultaneous Cooking of Multiple Dishes -- Estimation of Distributed Generation Using Complex-valued Network Inversion with Regularization -- A New Method of Cooperative PSO: Multiple Particle Swarm Optimizers with Inertia Weight with Diversive Curiosity -- A New Design Method for Train Marshaling Evaluating the Transfer Distance of Locomotive -- Cost-adjusted MIQ: A New Tool for Measuring Intelligence Value of Systems -- Harmony Search Algorithm with Various Evolutionary Elements for Fuzzy Aggregate Production Planning -- A Compression Technique for XML Element Retrieval -- Words-of-Wisdom Search Based on User’s Sentiment -- Configurable Application Designed for Mining XML Document Collections -- Integrated Approach for Privacy Preserving Itemset Mining -- Mining General Fuzzy Sequences Based on Fuzzy Ontology -- A Comparative Study of Density-based Clustering Algorithms on Data Streams: Micro-clustering Approaches -- A New Clustering Algorithm for Noisy Image Retrieval -- Page as a Meeting Place: Web Search Augmented with Social Communication -- The Game of N-Player White-Black Cutthroat and its Complexity -- Combinatorial Problems with Closure Structures -- Decidable Containment Problems of Rational Word Relations -- Pattern Matching Algorithms Using a Succinct Data Structure for Tree-Structured Patterns -- Network Traffic Screening Using Frequent Sequential Patterns -- Informative Gene Discover in DNA Microarray Data Using Statistical Approach -- High Capacity Image Steganography Based on Genetic Algorithm and Wavelet Transform -- Reduce Measurement Uncertainty of Ball Crater Method by Using Image Processing Techniques -- Decision-level Fusion Framework for Face Authentication System.
Keywords: Control engineering; Artificial intelligence; Electrical engineering; Control and Systems Theory; Artificial Intelligence; Electrical Engineering